Blood pressure and heart rates in neonates and preschool children: an analysis from 10 years of electronic recording. Issue 11 (12th August 2016) - Sottas, Cedric E.; Cumin, David; Anderson, Brian J.
Summary: Background: An acceptable systolic or mean arterial blood pressure for children 0–6 years during anesthesia is unknown. Accepted blood pressures reported in standard charts for healthy awake children may not apply to those undergoing anesthesia. Aim: Our goal was to define observed blood pressures (BP) and heart rate (HR) in children 0–5 years during anesthesia. Methods: Data from the electronic health record database were available for a 10‐year period from June 29, 2005 to July 22, 2015. A simple band‐pass filter was applied to remove artifact in the physiologic time‐series data for heart rate and blood pressure, with heart rate values 40 or above 250, mean or diastolic blood pressures below 20 or above 200, and systolic blood pressures below 30 or above 200 all excluded. For each anesthetic, the centiles of physiological variables (BP, HR) were calculated. Results: Data were available for 54 896 anesthetics in children 6 years and younger. There were 898 anesthesia reports available that included blood pressure measures immediately before induction. A larger number of anesthesia records ( n = 30 008) were available for intraoperative blood pressure recording. The BP decrease after anesthesia induction was most pronounced in infants 0–10 weeks of age where there was a mean arterial blood pressure (MAP) decrease of 16.6–34.5% (mean 28.6%). Systolic blood pressure decreased by 16.3–32.6% (mean 25.5%). Values above a systolic blood pressure of 60 mm Hg were only noted in half the neonates during anesthesia. Heart rates, both before and after anesthesia induction, were similar. Conclusion: Heart rate while under anesthesia appears a poor indicator for blood pressure changes. Recorded blood pressures in this current study, measured immediately before induction, were consistent with those in the literature. A mean MAP decrease of 28.6% was typical in those infants 0–10 weeks of age. Abstract :